Additional guarantees of observance of the rights and freedoms of specially designated subjects during the conduct of covert investigative (search) actions - Олександр Бабіков (Правові горизонти)
The article examines the additional guarantees provided to specially designated subjects—such as lawyers, journalists, medical professionals, and public officials—during covert investigative (search) actions. These subjects hold positions that require heightened protections due to the sensitive nature of their roles and responsibilities. The study analyzes the legal frameworks, both national and international, that aim to safeguard the rights and freedoms of these individuals when subjected to covert surveillance, searches, or other investigative activities. It emphasizes the need for stringent oversight mechanisms, legal safeguards, and procedural transparency to prevent abuse and ensure that any encroachment on rights is justified, proportionate, and lawful. The article also identifies gaps in existing regulations and suggests enhancements to better protect specially designated subjects, thereby balancing the needs of law enforcement with the preservation of fundamental human rights.